VD_FINDINFO Décision / 2013 / 512 vom 3. Dezember 2012 - VD Tribunal cantonal (2012)
RELIEF, DROIT TRANSITOIRE, LEX MITIOR, FORCE MAJEURE, JUGEMENT PAR DÉFAUT | 407 al. 1 CPP, 407 CPP, 408 CPP, 368 al. 3 CPP (CH), 452 al. 2 CPP (CH)